High-pressure behavior of energetic metal-organic frameworks: A first-principles study - Erkartal, Mustafa (Elsevier, 2026)
Exploring how energetic materials respond to compression provides fundamental insight into their stability, reactivity, and design of safer high-performance formulations. This study presents the first investigation of energetic metal-organic frameworks (EMOFs) under hydrostatic pressure. Periodic DFT-D calculations were performed to probe the structural, mechanical, and electronic properties of four 3D EMOFs with experimentally characterized crystal structures. Calculations included full lattice relaxation under pressures of 0-30 GPa, elastic tensor analysis to determine bulk and shear moduli, Hirshfeld surface and two-dimensional fingerprint analyses to examine intermolecular interactions, and electronic structure calculations to obtain pressure-dependent band gaps. Structural and electronic data were then correlated with literature-reported detonation and sensitivity values to elucidate the mechanisms linking lattice motifs, elastic compliance, and electronic stability to energetic behavior. The results reveal that hinge-like deformation, anisotropic elasticity, and pressure-stable band gaps enhance structural resilience, whereas pronounced band gap collapse under compression increases electronic polarizability and sensitivity. These insights provide a foundation for rational design and high-pressure exploration of EMOFs.
Keywords: Metal-organic frameworks (MOFs); High-pressure; First-principles; DFT; Energetic materials